Scanning electron microscopic screening; Can it be a taxonomic tool for identification of traditional therapeutic plants. Issue 4 (30th October 2020) - Jalal, Mehreen; Shaheen, Shabnum; Saddiqe, Zeb; Harun, Nidaa; Abbas, Moneeza; Khan, Farah
Abstract: The limiting factor in the utilization of herbal medicine is the risk of replacement or substitution of their plant resources. Therefore, the authentication of medicinal plants before its use in herbal medicines is essentially required. Hence, the prime objective of this study was to provide some reliable morpho‐anatomical and morpho‐palynological tools for the identification of nine traditional therapeutic plants of district Lahore. For this study, scanning electron microscopic and light microscopic approaches has been employed. Results reported great variations in qualitative and quantitative morpho‐anatomical features of the epidermal cell, stomatal complexes, trichomes, silica bodies and oil droplets. For example, Aegle marmelos L. can be distinguished from Cestrum diurnum L. based on epidermal cell shapes, as irregular cells in former and lobed cells shape in later one. Similarly unicellular, bicellular, and multicellular trichomes could be an identification basis for Cynodon dactylon L., Lantana camara L., and Pongamia pinnata L., respectively. In combination with these morpho‐anatomical characters, SEM‐based morpho‐palynological characterization also reported diagnostic value. Both the Aegle marmelos and Lantana camara possessed similar cell shape (irregular) but can be delimited based on their pollen morphology as spheroidal pollen was reported in Aegle marmelos whereas prolate in Lantana camara . Moreover, quantitative characters also aid well for species delimitation, such as prolate pollen found in both Cestrum diurnum and Terminalia chebula Retz. but both of these varied in their P/E ratio, that is, 0.97 and 0.88, respectively. The leaf epidermal characters in correlation with morph‐palynological traits showed potential for taxonomic resolution at the species level. Research Highlights: This study provides valuable morpho‐anatomical and morpho‐palynological tools for the nine traditional therapeutic plants of the district, Lahore, Pakistan. Light and scanning electron microscopic studies provided useful systematic data for the identification of studied plants. This systematic data include moprho‐anatomical and morpho‐palynological keys for the studied plants. This data can be used for future identification purposes. Abstract :